ACCOUNTABLE DATA AUTHORIZATION IN CLOUD ENVIRONMENTS: AN IDENTITY-BASED ENCRYPTION FRAMEWORK WITH EQUALITY TESTING (International Journal of Modern Computer Science and IT Innovations, 2025)
Ensuring secure and accountable access control in cloud environments is critical to protecting sensitive data from unauthorized use. This paper presents an identity-based encryption (IBE) framework enhanced with equality testing capabilities to support accountable data authorization. The proposed model allows data owners to encrypt information based on user identities while enabling controlled equality checks on ciphertexts without compromising data confidentiality. Additionally, a built-in accountability mechanism enables traceability of malicious activities and misuse of access privileges. Security and performance evaluations demonstrate that the framework provides strong data protection, efficient query operations, and practical enforcement of data accountability in distributed cloud systems.